Relationship Between Vertebral Fractures, Bone Mineral Density, and Osteometabolic Profile in HIV and Hepatitis B and C-Infected Patients Treated With ART - Dalla Grana, Elisa; Rigo, Fabio; Lanzafame, Massimiliano; Lattuada, Emanuela; Suardi, Silvia; Mottes, Monica; Valenti, Maria Teresa; Dalle Carbonare, Luca (Frontiers in Endocrinology, 2019)
Objective: The purpose of our study was to evaluate the alterations of bone metabolism and the prevalence of vertebral fractures in the population with HIV and hepatitis B and C seropositivity in treatment with antiretroviral drugs (HAART). Methods: We selected 83 patients with diagnosis of HIV, HBV, HCV infection. In all these patients biochemical examinations of phospho-calcium metabolism and a densitometry of lumbar spine were performed. We also evaluated lateral spine X-rays in order to analyze the presence of vertebral deformities and to define their severity. As a control group we analyzed the prevalence of vertebral fractures in a group of 40 non-infectious patients. Results: We selected 82 seropositive patients, 46 males and 37 females, with a median age of 55 ± 10 years. Out of these patients, 55 were infected by HIV, 12 were infected by HBV, 11 presented HIV and HCV co-infection and 4 were HCV+. The prevalence of hypovitaminosis D in the studied population was 53%, while the prevalence of osteoporosis and osteopenia was 14 and 48%, respectively. The average T-score in the fractured population was −1.9 SD. The viral load and the CD4+ cell count were respectively, directly, and inversely correlated with the number and severity of vertebral fractures. Antiretroviral therapy regimen containing TDF and PI was a significant determinant of the presence of vertebral deformities. The use of these drugs was also associated with lower levels of vitamin D and higher bone turnover levels compared to other antiretroviral drugs. Conclusions: HIV patients suffer from bone fragility, particularly at spine, independently by the level of bone mineral density. In this population, the T-score threshold for the risk of fracture is higher than that usually used in general population. For this reason, it would be indicated to perform an X-ray of the spine in order to detect vertebral deformities even in patients with a normal or slighlty reduced bone mineral density.